Reconstructing terrestrial nutrient cycling using stable nitrogen isotopes in wood - Gerhart Barley, Laci M.; McLauchlan, Kendra K. (My University, 2014)
Although recent anthropogenic effects on the global nitrogen (N) cycle have been significant, the consequences of increased anthropogenic N on terrestrial ecosystems are unclear. Studies of the impact of increased reactive N on forest ecosystems—impacts on hydrologic and gaseous loss pathways, retention capacity, and even net primary productivity— have been particularly limited by a lack of long-term baseline biogeochemical data. Stable nitrogen isotope analysis (ratio of ¹⁵N to ¹⁴N, termed δ¹⁵N) of wood chronologies offers the potential to address changes in ecosystem N cycling on millennial timescales and across broad geographic regions. Currently, nearly 50 studies have been published utilizing wood δ¹⁵N records; however, there are significant differences in study design and data interpretation. Here, we identify four categories of wood δ¹⁵N studies, summarize the common themes and primary findings of each category, identify gaps in the spatial and temporal scope of current wood δ¹⁵N chronologies, and synthesize methodological frameworks for future research by presenting eight suggestions for common methodological approaches and enhanced integration across studies. Wood δ¹⁵N records have the potential to provide valuable information for interpreting modern biogeochemical cycling. This review serves to advance the utility of this technique for long-term biogeochemical reconstructions.
Keywords: Nitrogen availability; Dendrochronology; δ¹⁵N; Dendroecology; Tree rings; Nitrogen deposition